2003
DOI: 10.1006/jcrs.2002.0475
|View full text |Cite
|
Sign up to set email alerts
|

On Predicting Roller Milling Performance IV: Effect of Roll Disposition on the Particle Size Distribution from First Break Milling of Wheat

Abstract: The breakage equation for roller milling allows prediction of the output particle size distribution from the feed particle size distribution in terms of a breakage function. Breakage functions were determined for First Break milling of hard and soft wheats under four roll dispositions: Sharp-to-Sharp (S-S), Sharp-to-Dull (S-D), Dull-to-Sharp (D-S) and Dull-to-Dull (D-D). The breakage functions were then used to predict the particle size distribution resulting from milling whole wheat samples at different roll … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 22 publications
1
15
1
Order By: Relevance
“…flour extraction rate (material <212 lm) and a corresponding increase in proportion of material larger than 2000 lm. This is as expected, as less breakage occurs at larger roll gaps, although the linear relationships are in contrast with the quadratic relationships observed for wheat milling (Campbell, Bunn, Webb, & Hook, 2001;Fang & Campbell, 2003). Milling at a roll gap of 0.1 mm released more than 18% flour, while maintaining 32.6% of the starting material as particles larger than 2000 lm.…”
Section: Break Roll Dispositioncontrasting
confidence: 54%
See 1 more Smart Citation
“…flour extraction rate (material <212 lm) and a corresponding increase in proportion of material larger than 2000 lm. This is as expected, as less breakage occurs at larger roll gaps, although the linear relationships are in contrast with the quadratic relationships observed for wheat milling (Campbell, Bunn, Webb, & Hook, 2001;Fang & Campbell, 2003). Milling at a roll gap of 0.1 mm released more than 18% flour, while maintaining 32.6% of the starting material as particles larger than 2000 lm.…”
Section: Break Roll Dispositioncontrasting
confidence: 54%
“…The effects of roller milling parameters on oat breakage were investigated using the versatile Satake STR-100 test roller mill (Satake Corporation, Hiroshima, Japan) Fang & Campbell, 2002, 2003, using a feeding rate equivalent to 300 kg h À1 , and fitted with either corrugated or smooth rolls. All rolls were manufactured to industrial configurations for wheat flour milling, having diameters of 250 mm, but only 100 mm in length (compared with 1000 mm typically for industrial roller mills).…”
Section: Dry Milling Equipmentmentioning
confidence: 99%
“…The cumulative percentage of undersize particles was also respectively, while x , just beyond the particle size 75 range measured, was estimated to be 3434 mm. These particle sizes are much larger than would be expected from First Break roller milling, for which the x is 50 typically in the range 500-1500 mm (Fang & Campbell, 2003a). This suggests that the mechanism of breakage in the SKCS is primarily compression, which tends to produce larger particles, in contrast to roller milling in which shear contributes significantly, as well as compression, the relative contributions depending on roll disposition (Fang & Campbell, 2002a,b, 2003a.…”
Section: Investigation Of the Effect Of Kernel Moisture Content On Brmentioning
confidence: 88%
“…Flour particle size distribution is an important indicator of the quality of high-ratio flour (Posner and Hibbs 1997), and commercial wheat flour samples are often characterized according to their particle size properties (Gaines 1985;McDonald 1994). It would therefore be useful to determine the relationship between flour yield and flour particle size distribution (Wu et al 1990;Fang and Campbell 2003;Kim et al 2004) and, revealed the effect of median flour particle size (µm) in wheat flour yield, so that the median flour particle size could be used as an index of flour yield in Japanese wheat breed programs, and developed a suitable method to evaluate flour yield of Japanese wheat (Nakamura 2014). Therefore, the aims of the current study are to investigate the differences of a median flour particle size between Japanese and Chinese common wheats, and could simply and quickly identify wheat genetic resources with high flour yielding in a systematic evaluation of N.A.R.O.…”
Section: Introductionmentioning
confidence: 99%